NICE public health guidance update. (30th July 2020) - Ali, Fizzah; Gabbay, Mark; Baillie, Nick
Abstract: This article highlights recent guidance from the National Institute for Health and Care Excellence (NICE). It highlights the organization's response to the COVID-19 pandemic and then provides a spotlight on workplace health in the context of long-term sickness absence and capability to work. It discusses some of the actions that need to be taken by a range of stakeholders in order to implement NICE guidance in this area and aid employees in ensuring good workplace health. The NICE guidance on workplace health, discussed in this article, predates the current pandemic. Comment is made specifically on fitness for work assessments, where the COVID-19 pandemic has posed a range of unique clinical challenges.